Advanced solution for urban gardens based on IoT systems, prediction algorithms and multi-criteria application - Andrei Danila; Robert Streche; Oana Orza; Cristina Dobre; George Suciu (Romanian Journal of Ecology & Environmental Chemistry)
Faced with the challenges posed by rapid urbanization and climate change, the U-GARDEN project offers an innovative solution for sustainable urban development through the implementation of smart urban gardens. The project utilizes an advanced multi-criteria application that combines real-time environmental monitoring with Internet of Things (IoT) technologies to optimize the management of green spaces and support healthy plant growth. A key component of this system is the implementation of algorithms to predict the risk of disease outbreaks in cultivated plants, based on the analysis of monitored data such as humidity, temperature, and air quality. The QGIS-based application allows for the identification of optimal locations for urban gardens, considering both socio-demographic and environmental factors, thereby facilitating efficient and sustainable management. Through active community involvement and the use of advanced technological tools, U-GARDEN contributes to improving urban quality of life and creating greener, more resilient cities. This article highlights the project's potential to transform urban spaces into productive and healthy environments through scalable and innovative solutions.